Implementation of Student Management in Increasing School Competitiveness at SMP Muhammadiyah 1 Kartasura - Utami, Rahayu; Shohib, Muhammad Wildan; Chehdimae, Hamdan (Jayapangus Press, 2025)
This research aims to determine effective student management in increasing school competitiveness at SMP Muhammadiyah 1 Kartasura. This research is qualitative research that uses the phenomenology approach. Various data collection techniques were used such as direct interviews, field observations, and documentation. The results of the research show that the Deputy Principal for Student Affairs at SMP Muhammadiyah 1 Kartasura applies student management to increase the school's competitiveness through the scope of student management, namely accepting new students, organizing classes, student orientation period, service development, school organization, student and graduate assessment. There are obstacles faced in the form of the difficulty of changing the mindset of students' parents in viewing private schools. So the Deputy Principal for Student Affairs is trying to socialize PPDB and design innovative and creative student programs so that it can display a good image of SMP Muhammadiyah 1 Kartasura.